Effective superior vena cava isolation using a novel C-shaped approach - Chen, Chun-Kai; Yu, Chih-Chieh (Frontiers in Cardiovascular Medicine, 2023)
Introduction. Superior vena cava (SVC) isolation has been proposed as part of the ablation strategy for atrial fibrillation. However, circumferential isolation of the SVC can lead to late-onset complications, such as SVC stenosis. Methods. We describe a detailed observation of the SVC conduction pattern and present a newly developed approach for SVC isolation that involves creating a C-shaped non-circumferential ablation line while sparing the anterolateral segment. Results. Twelve consecutive patients were included in the study, all of whom achieved bidirectional block during the ablation procedure. Discussion. This approach to SVC isolation is effective and has the potential to reduce ablation related complications; however, larger studies and long-term follow-up is warranted to confirm these findings.